Decoding the Digital Influence: Analyzing the Impact of Social Media Marketing on Consumer Behavior - Pandey, Bishesh; Sunar, Nar Bhupal; Sah, Prabhat Kumar (DAV Research Journal, 2026)
This study examines the effect of social media marketing strategies, such as influencer marketing, brand content and engagement, personalized marketing, and interactive campaign on consumer purchasing behavior in Nepal. The study has integrated the Technology Acceptance Model (TAM) and Theory of Planned Behavior (TPB). A quantitative approach was employed using cross-sectional data. A descriptive and causal research design was used. The data were collected through a structured online questionnaire from 250 active social media users in Nepal. Data were analyzed using correlation and multiple regression model. The results from the expanded sample robustly confirm that all four social media marketing strategies significantly influence consumer behavior with brand content demonstrating the strongest overall effect. Influencer marketing is significantly more effective among the younger consumers but its impact declines among older consumers. In contrast, personalized marketing becomes increasingly influential; however, brand content and interactive campaigns maintain a consistently positive and significant influence. The study, with enhanced statistical power, validates the integrated TAM-TPB framework, revealing that consumers prioritize peer-driven validation (influencers), while some consumers value utilitarian efficiency (personalization). Brand content is universally impactful, demanding strategic budget allocation. The study provides an actionable, empirically-strong framework for demographic targeting in understudied south Asian context.